Negligência unilateral pós-acidente vascular encefálico: atuação da Terapia Ocupacional - Oliveira, Tamara Pereira de [UNESP] (2014)
Unilateral Neglect Syndrome is one of the consequences of cerebral vascular accident (CVA) generally following right parietal lobe lesion, leading to the impairment of perceptive visual, spatial and attention functions. The patient affected does not realize the environmental stimuli on the contralesional hemibody. Occupational therapy plays an important role in caring for this patient, seeking the recovery of perception, attention and social engagement. This study aimed to describe and evaluate the results of occupational therapy intervention and treatment in a single Unilateral Neglect Syndrome post CVA patient. Data were obtained from a survey of the patient’s medical records and interviews of his therapist and caretaker. The analysis of the patient’s medical records and his therapist’s report showed that the patient responded satisfactorily to treatment, presenting a decrease of the left unilateral neglect at the end of the study period. The favorable outcome of the patient outlined the relevance of evaluating the effects of Occupational Therapy interventions for clinical unilateral neglect syndrome.